Impact of Road Infrastructure Pricing on Transport Planning - Poliak, Milos; Semanova, Stefania; Hernandez, Salvador; Pastuszkova, Eliska (Communications - Scientific Letters of the University of Zilina, 2015)
The paper deals with an issue of the impact of road infrastructure pricing on transport planning. The first part describes the history of road infrastructure pricing in the USA and the EU. The paper also describes an applicable methodology of toll rate determination in the EU. Further part of the paper deals with the factors affecting decision-making of carriers while planning a route of transport. Especially, it deals with a value of time savings and savings in fuel costs while deciding among several routes of transport. The proposal of a methodology for toll rate determination, taking into account the value of time savings for a carrier while using the toll road infrastructure, is elaborated in the next part of the paper. The methodology also takes into account savings in fuel costs of carriers.
Keywords: transport; toll; financing; factor; impact; decision-making